QUALITARIAN MODELS AND QUALITY CONTROL TOOLS FOR THE PRODUCTION PROCESS IN THE INDUSTRIAL ENTERPRISES - Shahobidinova Dilafruz Ekrinjon kizi; Qosimov Axtam Akramovich (Academia One, 2024)
In modern industry, one of the primary goals is to increase the efficiency of production processes and improve product quality. Quantitative models and quality control tools play a significant role in the improvement of industrial processes. This article presents the theoretical foundations of qualitarian models and quality management tools, methods of their use and practical examples.
Keywords: quality control; qualimmetric modeling; metrology; innovative technologies